The effects of Contingent Convertible (CoCo) bonds on insurers' capital requirements under Solvency II - Helmut Gründl; Tobias Niedrig (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2015)
The Liikanen Group proposes contingent convertible (CoCo) bonds as instruments to enhance financial stability in the banking industry. Especially life insurance companies could serve as CoCo bond holders as they are already the largest purchasers of bank bonds in Europe. The growing number of banks issuing CoCo bonds leads to a rising awareness of these hybrid securities among life insurers as they are increasingly looking for higher-yielding investments into bond-like asset classes during the current low interest rate period. Our contribution provides an insight for life insurance companies to understand the effects of holding CoCo bonds as implied by the Solvency II standards that will become effective by 2016.
urn:nbn:de:hebis:30:3-391006
Keywords: 330; Life insurance companies; Coco bonds; Solvency II